The impact of altitude conditions on performance in men`s and women`s professional padel - Escudero-Tena, A.; Martín-Miguel, I.; Sánchez-Alcaraz, B. J.; Lupo, C.; Conde-Ripoll, R.; Muñoz, D. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: The aim of this study was to analyze whether there are differences in performance indicators between matches played at different altitudes in professional padel. METHODS: Data were collected and analyzed based on players` sex, set number, and set score using video footage from the World Padel Tour (WPT), including open-access TV broadcasts and WPT`s YouTube channel. Performance indicators - such as break points won, errors, winners, and winning smashes - were recorded across 1122 sets (485 matches) from three WPT seasons (2020-2022). RESULTS: In men`s padel, altitude-related differences were observed in break points (P=0.005), break points won (P=0.002), and winners (P=0.002). In women`s padel, altitude-related differences were found in break points won (P=0.004), smashes (P<0.001), and winning smashes (P<0.001). Set number and set result were associated with variations in several performance indicators, depending on the tournament`s altitude (below or above 500 meters). CONCLUSIONS: These results represent reference data to help players and coaches train according to altitude conditions.